Profiling of seminal plasma proteins to identify the fertility of Simmental bull with low semen quality (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The present study analyzed the seminal plasma proteome and possible relationships between proteins and semen quality in azoospermic and normal Simmental bulls. Materials and Methods: Fresh semen plasma samples from the Lembang Artificial Insemination Center were used for this study, including one bull (76´ ejaculate) with very poor semen quality/ azoospermia (poor fresh semen/infertile; PFS) and three bulls with normal semen quality (normal fresh semen; NFS) for proteomic analysis using a pooled system (NFS-Stud) (60´ ejaculate). The only males obtained with very low quality or azoospermia (PFS) had sperm motility of